CURRENT TRENDS AND FUTURE DEVELOPMENTS ON (BIO-) MEMBRANES : SILLICA MEMBRANES: - Basile, Angelo editor; Ghasemzadeh, Kamran editor 631956; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2017)
Current Trends and Future Developments on (Bio-) Membranes: Silica Membranes: Preparation, Modelling, Application, and Commercialization discusses one of the most promising inorganic membranes, namely silica membranes, and their different applications. In the field of membrane separation technology, silica membranes play a key role in the future of the chemical industry as one of the most promising alternatives for separations at high temperatures and aggressive media.